Copper, Nickel and Manganese Residues in Tissues and Organs of Rabbits Dosed with Edible Clay - Suleiman P. I. Ogah; Faisal C. Emetumah (European Scientific Journal, ESJ, 2019)
The study examined the kinetics of Copper (Cu), Nickel (Ni) and Manganese (Mn) in tissues and organs of rabbits treated with edible clay from Enyigba, Ebonyi state Nigeria. Clay samples were obtained from Enyigba mine. Fifty four of the sampled rabbits were grouped into 3: group 1 and group 2 were administered with 2000 mg/kg and 4000 mg/kg of edible clay respectively while group 3 served as control. Concentrations of these metals were detected in the brain, heart, kidney, liver, lungs, skeletal muscle and blood of each of the rabbits using atomic absorption spectroscopy (AAS). One - way ANOVA was used in analyzing the concentrations with significant results (p < 0.05) recorded. The study results showed that while Cu concentrations were predominant in the liver (15.33±1.18 µg/g), kidney (8.25±1.18 µg/g) and heart (9.43±2.36 µg/g) of 2000 mg/kg treated rabbits on day 1 post-treatment, Ni concentrations were the highest among the three elements especially in the blood (221.59±17.05 µg/g) and skeletal muscle (153.41±19.68 µg/g) of 2000 mg/kg treated rabbits on day 1 post-treatment. Concentrations of Mn were mostly detected in the liver (13.99±4.85 µg/g) of 2000 mg/kg treated rabbits on day 1 post-treatment. Most of the concentration values increased in 4000 mg/kg treated rabbits on day 1 post-treatment. Elimination constants as well as half-life eliminations of the metals studied showed that absorbed elements were still present in most organs and tissues of treated rabbits. The study recommends research for possible microbial toxins that may be found in the edible clay studied.